Vibration Alert to the Brain: Evoked and Induced MEG Responses to High-Frequency Vibrotactile Stimuli on the Index Finger of Dominant and Non-dominant Hand - Kim, Min-Young; Kwon, Hyukchan; Yang, Tae-Heon; Kim, Kiwoong (Frontiers in Human Neuroscience, 2020)
Background: In recent years, vibrotactile haptic feedback technology has been widely used for user interfaces in the mobile devices. Although functional neuroimaging studies have investigated human brain responses to different types of tactile inputs, the neural mechanisms underlying high-frequency vibrotactile perception are still relatively unknown. Our aim was to investigate neuromagnetic brain responses to high-frequency vibrotactile stimulation, using magnetoencephalography (MEG). Methods: We measured 152-channel whole-head MEG in 30 healthy, right-handed volunteers (aged 20-28 years, 15 females). A total of 300 vibrotactile stimuli were presented at the tip of either the left index finger or the right index finger in two separate sessions. Sinusoidal vibrations at 150 Hz for 200 ms were generated with random inter-stimulus intervals between 1.6 and 2.4 s. Both time-locked analysis and time-frequency analysis were performed to identify peak responses and oscillatory modulations elicited by high-frequency vibrations. The significance of the evoked and induced responses for dominant and nondominant hand stimulation conditions was statistically tested, respectively. The difference in responses between stimulation condition was also statistically evaluated. Results: Prominent peak responses were observed at 56 ms (M50) and at 100 ms (M100) for both stimulation conditions. The M50 response revealed clear dipolar field patterns in the contralateral side with significant cortical activations in the contralateral primary sensorimotor area, whereas the M100 response was not as prominent as the M50. Vibrotactile stimulation induced significant suppression of both alpha (8-12 Hz) and beta (20-30 Hz) band activity during the mid-latency period (0.2-0.4 s), primarily in sensorimotor areas contralateral to the stimulation side. In addition, a significant alpha enhancement effect in posterior regions was accompanied with alpha suppressions in sensorimotor regions. The alpha suppression was observed in a broader distribution of cortical areas for the nondominant hand stimulation. Conclusion: Our data demonstrate that high-frequency vibrations, which is known to primarily activate Pacinian corpuscles, elicit somatosensory M50 and M100 responses in the evoked fields and induce modulations of alpha and beta band oscillations during mid-latency periods. Our study also suggests that the primary sensorimotor area is significantly involved in the processing of high-frequency vibrotactile information with contralateral dominance.